2018
DOI: 10.5380/rf.v48i3.55452
|View full text |Cite
|
Sign up to set email alerts
|

FOREST MANAGEMENT FOR THE CONSERVATION OF Araucaria angustifolia IN SOUTHERN BRAZIL

Abstract: Forest management is the legal instrument to propose interventions and conservation of tree species in natural forests; it is a requirement for the management of commercial forest plantations. Considering as objective the conservation with sustainable management and knowledge of the increment rates in forests with Araucaria angustifolia, growth models were fitted with the measures of ring increment data of 587 trees, covering all distribution diameter classes, in four sites in southern Brazil. These fitted mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…A higher growth rate than the values reported for the widespread invasive species P. undulatum, with a radial growth rate of 0.38 cm•year −1 , and an average of 8 years needed to attain breast height [2,4]. Therefore, other factors might be affecting growth and dispersal of those species, and a local comparison of growth rates would be needed, if the invasion process is to be better understood, since growth rate can provide a general representation of the growth dynamics at certain conditions (climate, hydrology, Forests 2019, 10, 538 of 21 soil, and successional stages) [78]. These analyses are essential to support the sustainable management and conservation of natural forests [78].…”
Section: Dendrometry and Dendrochronologymentioning
confidence: 99%
“…A higher growth rate than the values reported for the widespread invasive species P. undulatum, with a radial growth rate of 0.38 cm•year −1 , and an average of 8 years needed to attain breast height [2,4]. Therefore, other factors might be affecting growth and dispersal of those species, and a local comparison of growth rates would be needed, if the invasion process is to be better understood, since growth rate can provide a general representation of the growth dynamics at certain conditions (climate, hydrology, Forests 2019, 10, 538 of 21 soil, and successional stages) [78]. These analyses are essential to support the sustainable management and conservation of natural forests [78].…”
Section: Dendrometry and Dendrochronologymentioning
confidence: 99%
“…Another consequence is reflected in the rate of periodic diameter increase, as losses are more abrupt in smaller diameter trees than in those of larger size, due to competitive ability (Hess et al, 2018a). But the initial phase and growth acceleration when under continuous loss influence the tree's complete development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown this species' need for silvicultural intervention, since many diametric classes have already reached a growth stagnation point. Consequently, there is need to stimulate the growth of trees in lower diametric classes [42][43][44][45]. The complete lack of forest management contributes to the loss of diversity due to lower occurrence of sunflecks in the lower canopy layer and understory.…”
Section: Discussionmentioning
confidence: 99%